PENGARUH MODEL LEARNING CYCLE 5E DALAM PEMBELAJARAN FISIKA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA - Indri Indri Sari (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2015)
The purpose of this study was to determine the effect of  learning cycle 5e models to see the increasing of student’s achievement in physics learning of high school students. This study uses quasi experimental method. The population in this study is the high school students of class X in second semesters. The data  was collected by using  learning achievement test instruments and observation  sheet of student and teacher activities during the lesson.The results showed that students achievement increased after application of  learning cycle 5e model in dynamic electrical topic